A dualistic model of air technician safety behavior: Application of the reformulation of attitude theory. (December 2021) - Chen, Shu-Chuan
Abstract: Air technicians carry out critical responsibilities in aircraft maintenance. Their safety behavior is significantly and directly related to overall aviation safety performance. However, to date, only a limited number of studies have been devoted to discussion of air technician safety behavior issues. To gain an understanding of the related topics, in the current paper, Bagozzi's (1992) reformulation of attitude theory is applied to form a dualistic model identifying two types of stressors (i.e. challenge and hindrance) as the appraisal variables, and two types of job passion (i.e. obsessive and harmonious) as the emotional response variables. Air technician safety compliance and safety participation behavior are the targeted behavioral outcomes. A survey questionnaire is designed and distributed to collect data from Taiwanese maintenance technicians working for five national airlines. Structural equation modeling (SEM) is used to examine the hypothesized model. The results indicate that while the challenge stressor exerts more positive effects on harmonious job passion than on obsessive job passion, the hindrance stressor shows more negative effects on harmonious job passion than it does on obsessive job passion. Meanwhile, obsessive passion significantly and negatively affects air technician safety compliance and safety participation behavior. Harmonious passion, on the other hand, significantly enhances both types of safety behavior. The detailed discussion and implications of the findings are provided to serve as practical references for airlines when they are developing human resource management policies intended to enhance safety behavior on the part of maintenance crews. The research results will also be beneficial in terms of enriching the literature related to organizational safety behavior by offering the empirical evidence. Highlights: This paper applies reformulation of attitude theory to construct a dualistic model for considering the development of air technician safety behavior. While challenge stressor exerts more positive effects on harmonious job passion than on obsessive job passion, hindrance stressor shows more negative effects on harmonious job passion than it does on obsessive job passion. While obsessive passion significantly and negatively affects air technician safety compliance and safety participation behavior, harmonious passion significantly enhances both types of safety behavior.